Non-completed Studies: What Factors Affect Academic Success or Failure? - Edina Kovács (Debrecen University Press, 2019)
The ratio of early school leavers is 12.5 in Hungary, which means 22nd place within the EU28. Early school leaving is an important issue in all European countries, because those who finished their studies after primary education are more likely unemployed and it causes problems for both them and the society. Higher educational drop-out also an important issue, although for other reasons than early school leaving. It is even more difficult to find precise data on this: we don't know what proportion of the students is affected by this in Hungary. In this study I analyze the database of the Hungarian Youth Research 2016. This survey was conducted on a representative sample of 15-29 year olds, questioning 8,000 people, therefore, early school leavers and higher educational drop-outs should be found among the interviewees. The results show that early school leavers have significantly worse status both financial and cultural. Some of those who had finished only primary school think that they have successfully completed their studies. They answered that despite 18.3 percent of them have started a vocational training, which didn't finish. Despite the expectations, not much is known about the higher educational drop-outs. 4.5 percent of the interviewees did not answer the question of whether they had completed their studies: they are probably the drop-outs, but we can just assume that. The results show that they have better cultural status than the others.